Challenges of Democratization under International Supervision: The Case of Kosovo and East Timor. Issue 3 (3rd July 2019) - Kirakosyan, Marine
ABSTRACT: The article examines the role of international territorial administrations in the process of new regime building drawing on the cases of Kosovo and Timor-Leste. The cases under study have for a long time been under "internationalized regime" but are still far from being called democracies. The article sums up the basic challenges of democratization under extensive international supervision and seeks to answer whether international administration is a direct path to democratization or its continuing exercise may itself lead to labeling a newly independent state as a fragile or weak state. It concludes by stating that democratization is not simply a top-down process, and although the international efforts, particularly from the perspective of peace, stability, and institutional design, are decisive, the success of transition depends equally on domestic elites, and the values and principles the society adheres to.